2006
DOI: 10.1111/j.1468-3083.2006.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

What defines the quality of patient care in tinea pedis?

Abstract: Our study supports that azoles could be used as first-line treatment, as oxiconazole is very effective for both dermatophytes and C. albicans. Correlation between in vitro results and clinical outcomes of cases of dermatophytes is still to be established and interpretive breakpoints defined, in order to increase the quality of patient care in tinea pedis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although tinea pedis is not a life‐threatening condition, it is associated with difficulties in performing daily activities, and consequently, affects the quality of life 33 . Previous studies have shown relapses and failure to treat tinea pedis with routine antifungal agents 31,33‐35 . Therefore, reliable diagnosis and efficient treatment of tinea pedis are important.…”
Section: Discussionmentioning
confidence: 99%
“…Although tinea pedis is not a life‐threatening condition, it is associated with difficulties in performing daily activities, and consequently, affects the quality of life 33 . Previous studies have shown relapses and failure to treat tinea pedis with routine antifungal agents 31,33‐35 . Therefore, reliable diagnosis and efficient treatment of tinea pedis are important.…”
Section: Discussionmentioning
confidence: 99%
“…13 Few studies have examined the prevalence of occult tinea pedis in subjects who demonstrate both the absence of clinical symptoms and apparently healthy feet. 2,3,22 Carrier stage disease, or occult tinea pedis, can be considered to represent an early stage of the development of a dermatophytic infection because although subjects lack clinical symptoms and have apparently healthy feet, they are carriers of dermatophytes (positive mycological culture). The prevalence of occult tinea pedis is very similar to the clinical prevalence of tinea pedis.…”
Section: Discussionmentioning
confidence: 99%
“…Tinea pedis has a high prevalence in the general population and has been estimated to affect up to 25% of individuals. 2,3,22 Carrier stage disease, or occult tinea pedis, can be considered to represent an early stage of the development of a dermatophytic infection because although subjects lack clinical symptoms and have apparently healthy feet, they are carriers of dermatophytes (positive mycological culture). This implies that subjects with occult disease are able to transmit the disease despite being asymptomatic and demonstrating an absence of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations